Câncer: qual a percepção da criança sobre seu processo de adoecimento - Oliveira, Daiane Vargas de (2018)
In order to discuss and understand the experiences about the impact of difficult news communication in pediatrics, a qualitative, descriptive research was conducted with children undergoing antineoplastic treatment at the pediatric oncology service of the Hospital Universitário de Santa Maria (HUSM). The data saturation criterion was used to delimit the number of participants. Data collection was performed through semi-structured interviews and participant observation. Data analysis was performed through content analysis. Ethical principles were respected in order to protect all rights of participants, with formalization of participation through informed consent. Pediatric cancer elicit diffilculty family conflicts, so the research question is: How do children understand their illness process and delivering difficult news? And the hypothesis: Children understand their illness process and, in the majorty part, what it is to receive difficult news. This study concluded that, although there is much discussion about how to communicate difficulty news to children, the literature is still limited on this topic. In this study we also corroborate the capacity that children, for the majority, know they are ill, give opinions on the quality and difficulty of treatment, give suggestions for what can be improved and situations that displease them. Children can refer to physical and psychological symptoms, as well as extensive knowledge about medicantions used and their adverse effects. Neverthelles, we believe we have demonstrated from this research that children can and need to be heard and included in the process of communicating difficult news and the decisions that include their treatment. Children should participate in this process and not only their parents or legal guardians, since in their reports, although, most of the time, there is no open and frank communication, they realize and have knowledge of what happens in their enviroment.